Evaluate the Current Status and Importance of Macrophyte Floral Diversity of Meghadrigedda Reservoir at Andhra Pradesh, India - Karri Rama Rao; R. Ramachandra Rao; Karri Naga Mani (Innovations in Biological Science Vol. 9, 2024)
Aquatic macrophytes serve as a habitat for aquatic invertebrates as well as cover for fish. They also generate oxygen and provide food for some fish and other animals. They thrive in nutrient-rich water. In the natural environment, herbivorous and omnivorous fish might find edible plants for consumption. Aquatic plants can provide nutritious food for fish in aquariums or backyard ponds. Ipomoea aquatica, an aquatic weed, might be managed in an environmentally benign way by including it in a fish diet. Fish feed is critical to the long-term viability of aquaculture production. However, fish nutrition is crucial since feed is the costliest component of the aquaculture system, accounting for around 60% of total production costs. The young grass carp prefer duckweeds such as Lemna, Spirodela, Wolffia, and Azolla until they reach a greater size and can consume macrophytes. Aquatic weeds are potential fish and animal feed components that are extensively spread across Indian water bodies. The higher nutritional content of aquatic weeds has lately enabled fish meal to be largely or entirely substituted. Aquatic weed meal has 11 to 32% crude protein, 2.9 to 16.81% crude fat, 8 to 31% crude ash, and a very high amino acid, mineral, and vitamin content, depending on the components employed. Phytoremediation is a sustainable, cost-effective technology that uses plants to convert and stabilize pollutants in soil and water bodies. Aquatic plant species, primarily a broad group of macrophytes, have long served as indicators of water body health. A review of the ways in which aquatic macrophytes can be used in the food production process, including as human food, livestock fodder, fertilizer (mulch and manure, ash, green manure, compost, biogas slurry), and food for aquatic herbivores like adults and larval forms of fish, crab, and prawns.